A questao socioambiental e o sindicalismo rural em Pernambuco - Brasil - Silva, Tarcisio Augusto Alves (2016)
The paper discusses data from a research conducted with Fetape (Federação dos Trabalhadores na Agricultura do Estado de Pernambuco) to understand how environmental concerns have been incorporated into the union struggle. Information was obtained through literature review, document analysis of conference proceedings conducted by the federation, pamphlets, articles published in newspapers, claims guidelines, wage campaigns and collective bargaining. Semi-structured interviews were conducted with advisors, directors and organization of engineers in folders more directly related to the theme explored here. The results of the study indicate the environmental actions of the Federation has prioritized working conditions of small farmers and overlooked the reality of salaried rural workers linked mills and sugar cane plantations.